Optimal Control of Cervical Cancer Model with Vaccination and Screening - Kristanti, Karunia Theda; Trisilowati, Trisilowati; Widodo, Agus (The Journal of Experimental Life Science, 2020)
In this paper, an optimal control problem of a cervical cancer model with vaccination and screening as controls is discussed. This vaccine can stimulate the immune system to produce antibodies that can prevent the occurrence of human papillomavirus (HPV) infections, while screening is used as secondary prevention of early detection of cervical cancer cells so that treatment can begin immediately. The models were divided into two compartments, females and males. The female's compartment consists of susceptible, vaccinated, infected, screening, cervical cancer, and recovered females. Meanwhile, the male's compartment consists of susceptible, infected, and recovered males. The purpose of this optimal control was to minimize the number of infected females, infected males, and cervical cancer, as well as to minimize the cost of the controls. Optimal control was obtained by using the Pontryagin principle. Furthermore, an optimal control problem was solved numerically using the Forward-Backward Sweep method to determine the effect of vaccination and screening on the model. The results indicate that vaccination and screening as controls are effective in reducing the subpopulation of HPV infection, which can further reduce the occurrence of cervical cancer. Keywords: cervical cancer, vaccination, screening, optimal control